Species Composition and Inshore Migration of the Tropical Glass Eels (Anguilla spp.) Recruiting to the Jali River, Purworejo Regency - Indrawati, Ayuningtyas; Ibrahim, Putri Sapira; Yalindua, Fione Yukita; Kurniawan, Wanwan; Aisyah, Siti; Anggoro, Sutrisno; Saputra, Suradi Wijaya (Journal of Tropical Biodiversity and Biotechnology, 2024)
Purworejo Regency is located in the south coast of Java where rivers flow into the Indian Ocean. The Jali River in Purworejo becomes a migration route for eels where juvenile eels (glass eels) move from the ocean to freshwater passing through the estuary. During migration, glass eels will make efforts to survive, one of which is to manage their osmotic pressure (osmolarity). With regards to those, a study on the upstream migration of glass eels in Jali River was carried out. Glass eels samplings were conducted using hand-held lift nets at the new moon phase, from 20:00 pm to 4:00 am. Sampling stations included the estuary, a branch river, and below the dam. The osmolarity of both glass eels and media (river water) were measured. Furthermore, the chemical and physical parameters of the waters as the natural habitat for glass eels were also measured. Glass eel samples were then identified to species level. The results showed that glass eels entering the Jali River consisted of Anguilla bicolor bicolor and Anguilla nebulosa nebulosa with the former being the most common. Total length of glass eels ranged between 44.10 to 69.70 mm with total weights 0.08 to 0.54 g. Glass eel migration has a close relation with surface current and tide. The osmotic work level (OWL) of glass eels approaches 0.34 mOsm/l H2O which is close to iso-osmotic. This happened at salinity 0 o/oo so that the glass eels migrate to fresh water which has a lower salinity to achieve iso-osmotic condition.